THE RELATIONSHIP OF FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE AND FINANCIAL CAPABILITY TOWARD FINANCIAL WELL-BEING AMONG WORKERS: AN EMPIRICAL INVESTIGATION - Nor Shahrina Mohd Rafien; Shafinar Ismail (International Journal of Accounting, Finance and Business, 2021)
Financial well-being is explained where an individual can control the financialmatter on current life and future life as well without feeling worries on his or her financialsituation and it is vital to get better quality of life. Therefore, the aim of this study is toinvestigate the factors that influencing financial well-being among workers. The variables forthis study consist of financial attitude, financial knowledge and financial capability. A total of109 respondents aged between 21-40 years participated in the survey using purposive samplingtechnique among working persons in all states in Peninsular Malaysia. The data collected viaonline form. Multiple regression analysis is employed to analyse the data gathered. Thefindings revealed that there was an insignificant relationship between financial attitude andfinancial knowledge with financial well-being among workers. However, there was a significanteffect between financial capability with financial well-being among workers. The results couldbe used as guide to related government agencies, financial institutions, and the individual aswell in understanding the important of financial well-being to curb from facing financialproblem and to sustain the quality of life.